Survival in patients with colorectal cancer diagnosed by screening colonoscopy - Friedrich, Kilian; Gotthardt, Daniel; Eisenbach, Christoph; Stremmel, Wolfgang; Sieg, Andreas (Gastrointestinal endoscopy, 2015)
Background In Germany, screening colonoscopy was first established in 2002 as part of the national cancer screening program. Objective To evaluate whether colorectal cancer (CRC) survival differs when CRC is diagnosed by screening colonoscopy (S-CRC) versus diagnostic colonoscopy (D-CRC). Design Long-term, retrospective, multicenter, observational study. Setting Study centers: 10 private gastroenterology practices in Germany. Patients A total of 60 patients diagnosed with CRC during screening colonoscopy and 252 patients during diagnostic colonoscopy in 2002, 2003, and 2004. Interventions Colonoscopy. Main Outcome Measurements Survival of patients up to December 2013. Results Mean (± standard deviation [SD]) follow-up time was 81.0 (± 40.1) months. Union Internationale Contre le Cancer (UICC) stages I and II were found more often in S-CRC (81.6%) compared with D-CRC (59.9%; P < .002). Kaplan-Meier analysis showed significantly reduced overall survival for patients with D-CRC (mean [± SD] 86.9 [± 3.0] months; 95% confidence interval [CI], 81.0-92.8) compared with S-CRC (mean [± SD] 107.1 [± 4.9] months; 95% CI, 97.4-116.9; P = .003). When deaths not related to CRC were excluded, survival was still shorter for D-CRC patients (mean [± SD] 89.4 [± 3.0] months; 95% CI, 83.5-95.4) compared with S-CRC (mean [± SD] 109.6 [± 4.7] months; 95% CI, 100.2-119.0; P = .004). Limitations Retrospective study design. Conclusion In this long-term, retrospective study, patients with CRC diagnosed during screening colonoscopy lived significantly longer when compared with patients with CRC diagnosed during diagnostic colonoscopy.